Model NURS sebagai Alternatif Pembelajaran Keterampilan Membaca Bahasa Arab - Cholid, Cholid (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2022)
Arabic as a second language has different characteristics for students in Indonesia. To master the competence of reading Arabic texts, students must first master the Arabic Grammar before trying to understand the text they are reading. Furthermore, learning Arabic is often considered a scourge by most students. For that reason, this article aims to describe the NURS learning model as a solution for learning Arabic reading skills. The approach used in writing this article is a qualitative descriptive approach. Data were collected through documentation techniques and analyzed using content analysis by Miles and Huberman's theory. The conclusion of this article reveals that the NURS teaching model was designed based on constructivism and humanistic theories. This concept aligns with contextual learning and teaching that integrates student life into the learning process and materials. In addition, this model also allows teachers to become facilitators so the students can explore all existing potential to achieve learning objectives.